Ameliorating effects of low-dose ketamine administrations on opioid-induced memory impairments and neurodegeneration in mice - Uyar, Emre; Seker, Ugur; Ozhan, Onural; Acikgul, Muhammet Burak; Colak, Mehmet; Izci, Sevde Feyza; Parlakpinar, Hakan (Annals of Medical Research, 2023)
Aim: Opioids have indispensable roles in pain management. A strong link exists between opioid use and memory impairments, mainly with continuous use. This study investigated the effects of two opioid drugs, meperidine and fentanyl, on emotional memory functions, brain morphology, and the possible protective effects of low-dose ketamine in mice. Materials and Methods: A passive avoidance (PA) test was used to measure emotional memory functions following seven daily drug applications in 48 male Balb/C mice (30-35 g). Meperidine (10 mg/kg), fentanyl (0.3 mg/kg), ketamine (5 mg/kg), and combinations of ketamine with the opioids were intraperitoneally injected daily. No drugs were utilized during the testing days. Brain tissues were obtained after sacrification and put into diluted formalin solution for histopathological analysis. Results: Transfer latencies of the meperidine and fentanyl-treated groups in the PA test were lower than in the vehicle-treated group (p<0.01, p<0.05, respectively). Ketamine combined with meperidine had higher latencies than in the meperidine-treated group (p<0.05). The augmenting effects of ketamine were evident against fentanyl and meperidine-induced neurotoxicity as morphologic alterations were reduced. Conclusion: Low-dose ketamine may fend against opioid-induced neurotoxicity and emotional memory impairments, especially against meperidine, which can be a practical alternative to fentanyl in clinical settings.